GAME ONLINE DUEL MATEMATIKA BERBASIS WEB - Masnur Masnur; Tri Hariadi Purnomo (Universitas Halu Oleo, 2021)
Mathematics is a science that is very useful in everyday life. Mathematics lessons can be applied in various ways in everyday life. Hone skills in arithmetic can be done through interactive games such as games or games that are digital. This kind of game or game aims to provide education and a spirit of competition, especially in mathematics, by competing with other people to hone skills and speed in answering questions. A web-based math duel game made with HTML5, CSS3, PHP, and JavaScript technology. In this game, players can duel in Realtime with opponents in answering questions correctly and accurately by using a matching system according to the player's ranking. This Math Duel Web Game also has three types of games so that players have more playing options.